The Influence of Brand Image, Product Quality, and Social Media Promotion on Customer Satisfaction through Purchase Decisions at Viera Cake House in Pekanbaru City - Bagas Marcellino Rihandhika; Jushermi Jushermi; Henni Noviasari (Westscience Press, 2024)
One of the cake shops in Pekanbaru is Viera Cake House. There is a phenomenon related to the decline in the level of customer satisfaction at Viera Cake House. Low customer satisfaction will have an impact on decreasing purchasing decisions at Viera Cake House. This research aims to see the influence of brand image, product quality, and social media promotion on customer satisfaction through purchasing decisions at Viera Cake House in Pekanbaru City. The number of samples taken in the research was determined using the Lameshow formula and a sample of 100 consumers was obtained. The data analysis method used is Structural Equation Model (SEM) using SmartPLS software. The test results showed that brand image, product quality and social media promotion had a positive and significant effect on purchasing decisions. Purchasing decisions have a positive and significant effect on customer satisfaction. Product quality and social media promotion have a positive and significant effect on customer satisfaction through purchasing decisions. Brand image does not have a significant effect on customer satisfaction through purchasing decisions.